In-vitro Analysis of Antimicrobial Activities of Green Synthesized Silver Oxide Nanoparticles on some Microorganisms Found in Open Wound - Abdulmaleek, Rahama Orahachi; Okon, Idongesit Edem; Ndukwe, George Iloegbu; Adamma, Patricia; Ekwumemgbo, E. (Bumi Publikasi Nusantara, 2025)
The main obstacle to open wound healing is the formation of biofilms that are resistant to antimicrobial therapy. The use of silver nanoparticles, with their healing properties and broad antimicrobial effects, offers a new solution for wound infection control. This study aimed to investigate the antimicrobial activities of green-synthesized silver oxide nanoparticles (Ag2O-NPs) against bacteria (Staphylococcus aureus, Bacillus subtilis, Escherichia coli, and Pseudomonas aeruginosa) and fungi (Candida albicans) commonly found in open wounds in vitro. Ag2O-NPs showed significant zones of inhibition against the tested microorganisms. The minimum inhibitory concentration (MIC) values for bacteria were 3.75 mg/cm³ and 15 mg/cm³ for fungi, while the minimum bactericidal concentration (MBC) was 7.50 mg/cm³ for bacteria and 15.00 mg/cm³ for fungi. The results indicate that green-synthesized Ag2O-NPs possess antimicrobial activity, which could aid in wound healing.